Note:- 1) If y = sin(at) ; then dy/dx = a*cos(at)

2) If y = e^(at) ; then dy/dx = a*e^(at); where a = constant

Now,

f(t) = sin(e^t) + e^(sint)

f(t) is in the form of u + v ; where u = sin(e^t) & v = e^(sint)

Thus, by the addtion rule of differentiation;

f'(t) = u' + v'

Now, u = sin(e^t)

thus, u' = (e^t)*cos(e^t)........(1)

Also, v = e^(sint)

Thus, v' = cost*e^(sint).......(2)

Hence, f'(x) = u' + v' = [(e^t)*cos(e^t)] + [cost*e^(sint)]

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now